Theoretical and experimental analysis of structural joints of glued laminated pressed bamboo guadua for a housing project (2014)
The analysis of connections between elements of glued laminated pressed bamboo guadua (Guadua angustifolia Kunth) for a housing project is presented in this article. The analysis was carried out in four stages: design, load test, numerical simulation and finite element modeling. Design connection was developed using the allowable stresses method. In load test, displacements were measured in order to identify the behavior of connections for different load increments. Numerical simulation was performed in the software ETABS® with the loads used in the load test in order to determine the displacements at points experimentally instrumented in the test; each stage of load of test was simulated. Finally, the finite element modeling was performed in the software ANSYS®. Differences between the experimental results and those obtained with the simulations were found, which could be result of the differences between real conditions of the load test and design considerations as behavior completely rigid or pinned of connections.